Projeto e validação de software automotivo com o método de desenvolvimento baseado em modelos - Nunes, Lauro Roberto (2017)
The automotive heavy-duty vehicles have particular functionalities and aggressive environment application. To ensure better performance, safety and reliability to electronic embedded equipment, it is necessary to invest in methods and process improvements in automotive software development. Considering Model Based Design (MBD) as an ascending development method in automotive industry, this work looks towards contributions in requirements engineering, software optimization and validation, in order to prove the method and tools efficiency in the final product quality (heavy-duty vehicle). This work refers to the appliance of requirement engineering integration to the simulation (MIL - Model in the Loop), comparison between optimization in usual programming tools (IDE’s) and Model Based Design tools, validation and software code coverage, and an alternative way of increasing code coverage of a tested code.